Training of librarians as information literacy trainers - Pinto, María; Uribe-Tirado, Alejandro (Anuario ThinkEPI, 2011)
It is expected that one of the topics that will have a greater impact in this 21st century will be the training of graduate students, information professionals and users in general on information skills. This will underscore the value that universities and libraries offer to citizens. According to recent scientific literature the main trends that currently affect and will affect information trainers and professionals in the near future include: learning based on competencies and multi-literacy; pedagogic and didactic changes; technological developments; and all the aspects related to education, information, economic and technology policies and movements. Training in these matters and awareness of the theoretical and practical advances in information literacy are needed so that information professionals can achieve better information literacy and consequently be better information literacy trainers.
Keywords: Information literacy; Librarianship education; Continuous training; Trends; Information science.